The Effect of Information Technology and Service Quality on Customer Satisfaction at XYZ Company - Tenang Ribowo; Heri Ispriyahadi (Journal of Business, Management, & Accounting, 2022)
This study aims to investigate the effect of information technology and service quality on customer satisfaction at PT. XYZ which is engaged in online loans. The sample used in this study was 63 respondents who were obtained using the Slovin formula. The research data is primary data by distributing questionnaires to respondents whose data is tested using multiple regression analysis techniques. The results showed that both individually and simultaneously, information technology and service quality significantly affected customer satisfaction. This indicates that the better the quality of information technology and services will encourage increased customer satisfaction. Thus, companies must prioritize more superior technology and service quality to increase customer satisfaction, which will increase customer loyalty.